Digital Flipbook EcoSTEM-Inquiry Instructional Module: Improving Learning Motivation and Critical Thinking Skills in Grade 5 Elementary IPAS - Roro Setianingrum; Fery Muhamad Firdaus; Yulia Santi (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2025)
IPAS (Natural and Social Sciences) instruction at UPTD SDN 2 Labuhan Ratu I was heavily reliant on lecture-based methods occupying 73% of instructional time—with no integration of interactive digital media. Consequently, 62% of students exhibited low motivation, 58% faced challenges in critical reasoning, and the class average reached only 68.4, falling short of the minimum competency threshold (KKM) of 75. This study developed an EcoSTEM-Inquiry Digital Flipbook Instructional Module for IPAS, evaluated for validity, practicality, and effectiveness in fostering learning motivation and critical thinking among fifth-grade elementary students. A Research and Development (R&D) framework guided by the ADDIE model was employed. Participants comprised 19 students in the experimental group (Class VA, UPTD SDN 2 Labuhan Ratu I) and 19 in the control group (Class VB, UPTD SDN 2 Labuhan Ratu I). Instruments included expert validation rubrics, a 25-item ARCS-based learning motivation questionnaire (Likert 1–5), and a 15-item critical thinking test encompassing Facione's (2015) six indicators, with data analyzed via N-Gain, Independent Sample T-Test, and Cohen's d. The module achieved an expert validation mean of 4.43 (Very Good), a teacher usability rating of 89%, and a student response mean of 4.50. Effectiveness results showed significant gains in learning motivation (experimental N-Gain: 68.02% vs. control: 29.12%; t = 15.078; p < 0.05; d = 5.026) and critical thinking (experimental N-Gain: 62.20% vs. control: 20.89%; t = 8.648; p < 0.05; d = 2.883). The EcoSTEM-Inquiry Digital Flipbook Module is substantiated as valid, practical, and demonstrably superior to conventional instruction in improving both variables.